The Effect of Marjoram Aromatherapy and Deep Breathing Techniques on Blood Pressure of Hypertensive Patients - Firza Pinamiranti; Irna Nusanti; Wati Jumaiyah; Dhea Natashia; Ii Ismail; Noviana Noviana (Indonesian Journal of Global Health Research, 2025)
Hypertension is a major cause and risk factor for death worldwide. Nonpharmacological therapy of hypertension to reduce blood pressure of hypertensive patients, one of which is marjoram aromatherapy and deep breathing techniques that have proven effective in hypertensive patients. Objective: The purpose of the study was to determine the effect of marjoram aromatherapy and deep breathing techniques on blood pressure of hypertensive patients. Methods: This type of research is a quasy experiment with a one group pretest-postest design without control group approach, the number of samples was 20 respondents using total sampling. The data collection technique used is observation through blood pressure measurement. Hypothesis analysis is normality test, One Way Repeated Measurement (ANOVA), and multiple linear regression. Results: There is an effect of marjoram aromatherapy and deep breathing techniques on blood pressure of hypertensive patients (p-value <0.05). Conclusion: There is an effect of marjoram aromatherapy and deep breathing techniques on the blood pressure of hypertensive patients. Marjoram aromatherapy interventions and deep breathing techniques can be socialized in hospitals and can be done independently at home to reduce blood pressure in people with hypertension.